Near‐Infrared Light–Induced Sequential Shape Recovery and Separation of Assembled Temperature Memory Polymer Microparticles. Issue 8 (17th March 2020) - Zhou, Cihui; Ni, Yaru; Liu, Wenting; Tan, Bin; Yao, Mengchen; Fang, Liang; Lu, Chunhua; Xu, Zhongzi
Abstract: Light‐induced, shape‐changing polymeric microparticles have many applications. Here, the near‐infrared (NIR)‐light‐triggered sequential recovery and separation of assembled large and small polymer microparticles using cross‐linked blends of poly(ethylene‐vinyl acetate) and trans ‐polyisoprene as temperature memory polymers as well as two NaYF4 based up‐conversion nanoparticles (UCPs) to provide luminescent and photothermal effects are reported. Under irradiation of NIR light with a low light power density, small particles assembled onto the compressed large one recover first due to the low switching temperature ( T sw ) arising from the temperature–memory effect. The small particles can separate from the underlying large particle in flowing aqueous media. The recovery of the large particle occurs at a high power density. Two UCPs of NaYF4 : 20Yb, 0.2Tm, 5Gd and NaYF4 : 18Yb, 2Er, 5Gd facilitate the detection of small and large microparticles via providing blue and green light emissions, respectively. This work can expand the applications of light‐induced shape‐changing polymer microparticles in the biomedical field, controlled catalysis, microfluidic devices, and so on. Abstract : Near‐infrared light induces the sequential shape recovery and separation of assembled large and small polymer microparticles using cross‐linked blends of poly(ethylene‐vinyl acetate) and trans‐polyisoprene as temperature memory polymers as well as two NaYF4 ‐based upconversion nanoparticles (UCPs) to provide luminescent and photothermal effects.